Latihan Dasar Kepemimpinan OSIS SMK Mandala Bhakti Surakarta - Bangun Prajadi Cipto Utomo; Tri Djoko Santosa (CV. Multi Kreasi Media, 2024)
OSIS is the largest independent organization in the school environment which provides a shelter for other organizations that exist under the supervision of OSIS. The progress and withdrawal of the OSIS depends on the management performance and leadership qualities of the OSIS administrators who are selected students who have passed the selection and are deemed worthy and capable of managing the OSIS for 1 (one) year of service. The event was carried out as part of the Tri Dharma of Higher Education and collaboration between SMK Mandala Bhakti Surakarta and Duta Bangsa University Surakarta. The result of this Community Service objective is that OSIS administrators understand more about leadership in organizations, and at the same time provides practice on how to be a good leader in organizations. In addition, it provides an understanding of how they become good members of the organization.